PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTARDI BURSA EFEK INDONESIA PERIODE 2022-2023 - Sembiring, Yan Christin Br; Maduwu, Esta; Naibaho, Pani Romauli Elisabet; Lumbangaol, Romasi (UNIKA Santo Thomas, 2025)
This research aims to examine the influence of Corporate Social Responsibility (CSR) on Profitability. The population in this research is food and beverage companies listed on the Indonesia Stock Exchange for the 2022-2023 period with a population of 95 companies. The total sample was 65 companies in the 2 years research period with 130 observations. Sampling used purposive sampling technique. The analytical methods used are descriptive statistical tests, classical assumption tests which include normality tests, autocorrelation tests, and heteroscedasticity tests. Using simple linear regression analysis, and hypothesis testing, using SPSS version 20 to process data. The data analysis technique used is simple linear regression and hypothesis testing uses the t statistical test with a significance level of 5%. The results of this research show that CSR has a negative and insignificant effect on Return on Assets (ROA), a negative and insignificant effect on Return on Equity (ROE), and a negative and insignificant effect on Net Profit Margin (NPM) in food and beverage companies listed on the Indonesian Stock Exchange in 2022-2023.